Legal Protection of the Rights of the Suspect Against the Implementation of the Return of the Case File from the Public Prosecutor to the Investigator Repeatedly - Fetty Faulina Yekti; Emmilia Rusdiana (Universitas Negeri Surabaya, 2024)
The purpose of this study is to analyze whether or not the Circular Letter of the Deputy Attorney General for General Crimes Number SE-3/E/EJP/11/2020 of 2020 concerning prosecutor's instructions (P-19) at the pre-prosecution stage is carried out once in handling general criminal cases and legal protection for suspects for the return of case files from the public prosecutor to the investigator more than once. This research method is normative juridical. The results and discussion show that pre-prosecution restrictions through Circular Letter of the Deputy Attorney General for General Crimes Number SE-3/E/EJP/11/2020 of 2020 concerning prosecutor instructions (P-19) at the pre-prosecution stage are carried out once in handling general criminal cases are non-binding so that they can be easily deviated from and the form of legal protection for suspects whose rights are violated by the return of alternating case files is that the investigator issues an Order to Terminate Investigation (SP3), provide rehabilitation and coordinate well with the public prosecutor as stated in Article 109 paragraph (1) of Law Number 8 of 1981 concerning the Criminal Procedure Code.